2010
DOI: 10.1007/s11947-009-0316-6
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Caribbean Sweet Potato (Ipomoea batatas (L) Lam) Starches

Abstract: The proximate compositions and physicochemical properties of 21 Caribbean sweet potato (Ipomoea batatas (L) Lam) starches were investigated. Proximate composition, amylose, reducing and non-reducing sugars were determined using standard methods. Swelling power and solubility were evaluated and pasting properties of the starches were determined using Rapid Visco Analyzer. Moisture (8.0-12.4%), protein (0.0-0.2%), ash (0.1-0.5%), and reducing (0.3-2.3%) and non-reducing sugar (0.1-0.2%) contents of starches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…Swelling power and solubility can provide evidence in assessing the extent of interaction between starch chains within the amorphous and crystalline domains of the starch granule (Ratnayake et al 2002;Adebisola et al 2010).…”
Section: Physicochemical Properties Of Starchesmentioning
confidence: 99%
“…Swelling power and solubility can provide evidence in assessing the extent of interaction between starch chains within the amorphous and crystalline domains of the starch granule (Ratnayake et al 2002;Adebisola et al 2010).…”
Section: Physicochemical Properties Of Starchesmentioning
confidence: 99%
“…Limited studies have been reported on characterization of arrowroot starches (14,16). Starches isolated from some rhizomes and tubers like yam, cocoyam, cassava, sweet potato, and ginger were characterized (8,17). However, maranta starch has received less attention despite its enormous potential in food applications.…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato roots can be processed into products with improved characteristics and longer shelf life. The occurrence of natural hybrids and mutations and artificial selection of sweet potatoes have resulted in the existence of large number of cultivars [2,3]. These cultivars differ in many of their properties, ranging from the physical appearance and texture of the tuber to structure-function properties of the starch [4].…”
Section: Introductionmentioning
confidence: 99%